2020
DOI: 10.21673/anadoluklin.735140
|View full text |Cite
|
Sign up to set email alerts
|

Tüm Dünyada Sağlık Çalışanları Covid-19 Nedeniyle Hayatını Kaybediyor

Abstract: Frontline healthcare workers (HCWs) play the most essential role, especially since the Covid-19 breakout, providing care for patients all over the world. In the context of Covid-19, thousands of healthcare workers were infected and hundreds of them have died. Since there is no systematic reporting system of infected healthcare workers, it is difficult to track down current and accurate data. While national reports help to understand the severity of the infection among HCW, yet global data is lacking. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…3,4 It is reported that healthcare professionals, who have a key role in this process, are among the groups with the highest potential to be affected, as in pandemics in the past, and hundreds of them died due to the pandemic. 3,5,6 Phobias are anxiety disorders that are characterized by a persistent, intense fear of a substance or circumstance. 7 Phobias brought on by environmental causes can be triggered by disasters like the COVID-19 epidemic.…”
mentioning
confidence: 99%
“…3,4 It is reported that healthcare professionals, who have a key role in this process, are among the groups with the highest potential to be affected, as in pandemics in the past, and hundreds of them died due to the pandemic. 3,5,6 Phobias are anxiety disorders that are characterized by a persistent, intense fear of a substance or circumstance. 7 Phobias brought on by environmental causes can be triggered by disasters like the COVID-19 epidemic.…”
mentioning
confidence: 99%
“…Uluslararası kaynakları birleştirerek toplam 52 ülkeden elde ettikleri verilere göre 27 Nisan 2020 tarihine kadar 708 sağlık çalışanının COVID-19 nedeniyle hayatını kaybettiği, hayatını kaybedenlerin 365'inin (%51,5) doktor, 126'sının (%17,9) hemşire olduğu belirtilmiştir. 15 Bu tema altında incelenen diğer bir alt başlık ise hemşirenin COVID-19 aşısı olmasıydı (n=15, %17). 16 Hemşirelerin, COVID-19 aşısı olması ile ilgili haberlerin çoğu yurt dışı kaynaklı haberdi.…”
Section: Discussionunclassified
“…[7] In another study, it was pointed out that 708 healthcare workers died from COVID-19 worldwide until April 27, 2020; 365 (51.5%) of these were physicians, and 126 (17.9%) were nurses. [8] In our study, we investigated in which operations and age group the surgeons serving during the epidemic were under a greater risk. The patients who need a surgical operation for non-deferrable diseases such as malignancy, in particular, isolate themselves in preventive quarantine and constitute a lower risk in terms of infecting the surgical team.…”
Section: Discussionmentioning
confidence: 99%